Peningkatan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Problem Based Learning (PBL) Pada Materi Barisan Dan Deret - Wahyu Anugerah Sianipar; Asrin Lubis (Departement of Mathematics Education, 2024)
This research aims to find out how to improve student mathematics learning outcomes through the Problem Based Learning model in class VIII-4 SMPN 2 Bandar Khalipah on Lines and Series material. This research is Classroom Action Research (PTK). The subjects in this research were 20 students in class VIII-4 of SMPN 2 Bandar Khalipah. The instruments in this research consisted of tests and observation sheets. The results of the initial ability test show that the average student mathematics learning ability is 28.44, including the Very Poor ability category. In cycle I, the test results showed that the average student mathematics learning ability was 74.06, including the Sufficient ability category. In cycle II, the test results showed that the average student mathematics learning ability was 80.94, including the Good ability category. From the observation results, it was found that the average value of the learning process in cycle I was 2.71, including the Good category, and cycle II was 3.32 in the Very Good category. With this increase, it was concluded that by implementing the problem based learning model there was an increase in the mathematics learning outcomes of class VIII-4 students at SMPN 2 Bandar Khalipah.